2009
DOI: 10.3844/jssp.2009.223.235
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Satisfaction with Public Health Care in China

Abstract: Problem statement:Consumer satisfaction is regarded as one of the ultimate goals that all health system should strive for (Hsiao, 2003), it reflects the effectiveness of the health system in consumers' prospect. Yet public health care services in developing countries including Greater Mekong Sub-region (GMS) have failed to achieve adequate level of services. China, for example, satisfaction of public health care is considerably low. To improve public participation and effectiveness of the undergoing health ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…There was a significant association between satisfaction with RS and age, where younger age appear to be more satisfied with RS. This result is different than other studies that shows an association between satisfaction with increasing age (Jiang et al, 2009;Greenhow et al, 1998). Also there was significant association with gender as females shows higher satisfaction than males.…”
Section: The Satisfaction Rate Wascontrasting
confidence: 91%
“…There was a significant association between satisfaction with RS and age, where younger age appear to be more satisfied with RS. This result is different than other studies that shows an association between satisfaction with increasing age (Jiang et al, 2009;Greenhow et al, 1998). Also there was significant association with gender as females shows higher satisfaction than males.…”
Section: The Satisfaction Rate Wascontrasting
confidence: 91%
“…For example, the National Health Services Survey showed that in 2003 nearly half of respondents who had suffered health problems 'did not visit doctors for recommended treatment' and more than 10 per cent of patients 'did not have any treatment' because of financial difficulties (Zhao, 2006). Another study reported that of the 569 respondents in Kunming city in 2007, 58 per cent of them were dissatisfied/very dissatisfied with the affordability of public health care delivery (Jiang et al 2009). Thus, significant improvement in China's public health care delivery is urgent.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that of the 569 respondents in Kunming city in 2007, 58 per cent of them were dissatisfied/very dissatisfied with the affordability of public health care delivery (Jiang et al . 2009). Thus, significant improvement in China's public health care delivery is urgent.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is also partly due to the fact that few implementation methodologies can meet the requirement of the difficult problem-solving process, since this problem-solving process involves an analysis of interdependent activities whose critical attributes include intangible elements. In the literature, a number of implementation methodologies have been applied to solve China’s institutional problem of health care provider selection, such as qualitative methods [7] and statistical methods [21]; however, none of them could handle the possible interactions among decision factors/constraints in the complex multi-stage setting in this problem, so they were not the effective implementation methodologies that could help the decision maker effectively promote various experts’ views into various optimal solutions to China’s institutional problem of health care provider selection.…”
Section: Introductionmentioning
confidence: 99%